Pengaruh Work-Family Conflict dan Family-Work Conflict Terhadap Kepuasan Kerja Pada Pekerja Formal Perempuan Etnis Bali Di Kota Praya - Putri, Ni Wayan Krisnitha; Nurmayanti, Siti (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This research was conducted to determine the factors that can influence job satisfaction. This research aims to empirically test the influence of Work-Family Conflict and Family-Work Conflict on job satisfaction. This Work-Family Conflict research uses primary and secondary data obtained through distributing questionnaires to respondents, who are ethnic Balinese female workers in the city of Praya. The population in this study were ethnic Balinese female workers who lived in the city of Praya. This research is quantitative research. The sample used was 79 people determined based on saturated sampling techniques. The sample range used in this research is ethnic Balinese female workers in the city of Praya with the criteria: female workers who are married, live with their husband, have been married for at least one year and have at least one child. The analysis technique used in this research is multiple linear regression. The research results show that Work-Family Conflict has a negative and insignificant effect on job satisfaction, and Family-Work Conflict has a negative and insignificant effect on job satisfaction.